Infrared Thermography in the Evaluation of Dental Socket Healing After Photobiomodulation Therapy: A Case Report - Carvalho, Giovanna Rodrigues de; Rodrigues, Wictor Nogueira; Barboza, João Victor Melo; de Góis Nery, Cláudio; Moreira, Francine do Couto Lima; Roriz, Virgílio Moreira (Journal of Lasers in Medical Sciences, 2021)
Introduction: The aim of this article was to evaluate the efficacy of photobiomodulation therapy (PBMT) in the alveolar tissue healing process post-extraction using infrared thermography (IT). Case Presentation: A 36-year-old male patient had teeth extractions (18 and 28). Four PBMT sessions (660 nm; 2 J per tooth) were performed in the region of tooth 28 and recorded with thermographic images to compare the healing process, bilaterally. In the first two postoperative sessions, the temperature was higher (hyperradiant) on the left side (treated). After the third laser application, the left side was hyporradiant. In a later session, the treated side became hyperradiant compared to the control side. The alveolus of tooth 28 showed more rapid healing than tooth 18 over a period of 60 days. Conclusion: IT can be used to detect the favorable effect of PBMT on accelerating the healing process in the alveolus within 60 days after the tooth extraction. DOI: 10.34172/jlms.2021.11